Blockade of IL-33R/ST2 Signaling Attenuates Toxoplasma gondii Ileitis Depending on IL-22 Expression - Ryffel, Bernhard; Huang, Feng; Robinet, Pauline; Panek, Corine; Couillin, Isabelle; Erard, François; Piotet, Julie; Le Bert, Marc; Mackowiak, Claire; Torres Arias, Marbel; Dimier-Poisson, Isabelle; Zheng, Song Guo (Frontiers in Immunology, 2019)
Oral T. gondii infection (30 cysts of 76 K strain) induces acute lethal ileitis in sensitive C57BL6 (B6) mice with increased expression of IL-33 and its receptor ST2 in the ileum. Here we show that IL-33 is involved in ileitis, since absence of IL-33R/ST2 attenuated neutrophilic inflammation and Th1 cytokines upon T. gondii infection with enhanced survival. Blockade of IL-33R by neutralizing ST2 antibody in B6 mice conferred partial protection, while rec-mIL-33 aggravated ileitis. Since IL-22 expression further increased in absence of IL33R, we blocked IL-22 by neutralizing antibody, which abrogated protection from acute ileitis in IL-33R/ST2 deficient mice. In conclusion, severe lethal ileitis induced by oral T. gondii infection is attenuated by blockade of IL-33RST2 signaling and is mediated in part by IL-22.